Alternative linearisations for the operating cost function of UC problems. Issue 8 (9th June 2017) - Geng, Zhaowei; Conejo, Antonio J.; Xia, Qing
Abstract : The cost of a generating unit as a function of its power output is generally non‐linear and discontinuous. Therefore, the objective function of a unit commitment (UC) problem is generally non‐linear and discontinuous as well. The authors describe two efficient piecewise‐linear formulations of the objective function of an UC problem that are not found in the power literature. These formulations allow representing non‐convexities and discontinuities. They compare these formulations with a common one in the power literature. They show the advantage of the proposed formulations for both deterministic and stochastic UC problems.